Spectrophotometric determination of phosphate in presence of arsenate - Subedi, Krishna; Adhikari, Sujata; Dhungana, Sabin; Poudel, Bhoj Raj; Pokhrel, Megh Raj (Scientific World, 2022)
A simple and sensitive spectrophotometric method has been optimized for the determination of phosphate in the presence of arsenate. This method is based on the formation of phosphomolybdate complex from phosphate and added molybdate ion in an acidic medium, followed by the reduction of the complex with hydrazine hydrate. The system obeys Lambert-Beer’s law in the concentration range 60-1080 ppb. The optimized volume of different reagents was 3.5 mL of 0.25% ammonium molybdate, 1.5 mL of 0.25 N sulfuric acids, and 1 mL of 0.5 M of hydrazine hydrate. The time required for the full-color development was 15 minutes at 30oC. The arsenate interference was successfully removed by using sodium thiosulphate and sodium metabisulfite below the arsenic concentration of 100 ppb. 0.2 mL of 1 M sodium metabisulfite and 1 mL of 0.1 M sodium thiosulphate were found to be the optimum volume for inhibiting arsenate interference below 100 ppb arsenate concentration.